Pelatihan Deteksi Dini Gangguan Jiwa Pada Kader Kesehatan Jiwa di Kelurahan Joyontakan[Early Detection Training for Mental Disorders for Mental Health Cadres in Joyontakan Village] - Ardika, Noviana Ayu; Prasetyo, Rian (UKInstitute, 2025)
Abstract. The increase in people with mental disorders, according to data from the Regional Health Research Institute (Rikesda), has reached 7%. In Central Java, the number of people with severe mental disorders is estimated to reach 450,000, with 8.7% of the population suffering from schizophrenia. Therefore, Central Java is one of the provinces with the fifth highest number of people with mental disorders. The purpose and focus of this activity is to increase the knowledge of mental health cadres about detecting mental disorders, improve their skills in recognizing the signs of mental disorders, and improve their communication skills with families with mental disorders at home. The results obtained from this community service include an increase in cadre knowledge and skills in early detection of mental disorders in the community, from 40% to 85%. This community service is very beneficial in the future if new cases of mental disorders in the community arise, cadres will be better prepared and understand what to do. Abstrak. Peningkatan penderita gangguan jiwa berdasarkan data Rikesda mencapai 7%. Di Jawa Tengah gangguan jiwa yang berat diperkirakan mencapai 450 ribu orang, dengan 8,7% penduduk menderita skizofrenia. Oleh karena itu jawa Tengah menjadi salah satu provinsi dengan urutan kelima jumlah penderita gangguan jiwa terbanyak. Tujuan dan fokus dari kegiatan ini adalah untuk meningkatkan pengetahuan kader kesehatan jiwa tentang deteksi gangguan jiwa, meningkatkan keterampilan kader dalam melihat tanda gejala gangguan jiwa, dan meningkatkan keterampilan dalam komunikasi dengan keluarga dengan gangguan jiwa dirumah. Hasil yang didapatkan dari pengabdian kepada masyarakat ini terdapat peningkatan pengetahuan kader dan keterampilan kader dalam deteksi dini gangguan jiwa dimasyarakat yang sebelumnya 40% menjadi 85% . Pengabdian kepada masyarakat ini sangat bermanfaat kedepannya jika di masyarakat terdapat kasus baru tentang gangguan jiwa maka kader akan lebih siap dan paham apa yang harus dilakukan.